Transcriptomic Insights Into Root Development and Overwintering Transcriptional Memory of Brassica rapa L. Grown in the Field - Liu, Lijun; Pu, Yuanyuan; Niu, Zaoxia; Wu, Junyan; Fang, Yan; Xu, Jun; Xu, Fang; Yue, Jinli; Ma, Li; Li, Xuecai; Sun, Wancang (Frontiers in Plant Science, 2022)
As the only overwintering oil crop in the north area of China, living through winter is the primary feature for winter rapeseed. Root is the only survival organ during prolonged cold exposure in winter to guarantee flowering in spring. However, little is known about its root development and overwintering memory mechanism. In this study, the root collar tissue (including the shoot apical meristem) of three winter rapeseed varieties with different cold resistance, i.e., Longyou-7 (strong cold tolerance), Tianyou-4 (middle cold tolerance), and Lenox (cold-sensitive), sampling at pre-winter period (S1), overwintering periods (S2-S5) and re-greening stage (S6), were used to identify the root development and overwintering memory mechanisms and seek the candidate overwintering memory genes by measuring the root collar diameter and RNA sequencing. Results showed that S1 to S2 stage was the significant developmental stage of the root as the root collar diameter increased slowly at S3-S5 stages, and the root developed fast in the strong cold resistance variety than weak cold resistance variety. Subsequently, RNA-seq analysis revealed a total of 37,905, 45,102 and 39,276 differentially expressed genes (DEGs) compared to the S1 stage were identified in Longyou-7, Tianyou-4 and Lenox, respectively. Function enrichment analysis showed that most DEGs are significantly involved in phenylpropanoid biosynthesis, plant hormone signal transduction, MAPK signaling pathway, starch and sucrose metabolism, photosynthesis, amino sugar and nucleotide sugar metabolism, spliceosome, ribosome, proteasome and protein processing in endoplasmic reticulum pathways. Furthermore, phenylpropanoid biosynthesis and plant hormone signal transduction pathways were related to the difference in root development of three varieties, and DEGs involved in photosynthesis and carbohydrate metabolism processes may participate in overwintering memory of the Longyou-7 and Tianyou-4, and spliceosome pathway may contribute to the super winter resistance of Longyou-7. Transcription factor enrichment analysis showed that the WRKY family made up the majority at different stages and may play an important regulatory role in root development and overwintering memory. These results provide a comprehensive insight into winter rapeseed's complex overwintering memory mechanisms. The identified candidate overwintering memory genes may also serve as important genetic resources for breeding to further improve the cold resistance of winter rapeseed.